The complete chloroplast genome of Chamaesium paradoxum. Issue 1 (2nd January 2019) - Zheng, Hongyi; Guo, Xianlin; He, Xingjin; Yu, Yan; Zhou, Songdong
Abstract: Chamaesium paradoxum H. Wolff is an endemic species naturally distributed in China. The complete chloroplast genome sequence of C. paradoxum was generated by de novo assembly using whole genome next generation sequencing data. The complete chloroplast genome of C. paradoxum is 153, 512 bp in length, consisting of a pair of inverted repeats (IRs, 25, 987 bp) separated by a large single-copy region (LSC, 84, 162 bp) and a small single-copy region (SSC, 17, 376 bp). There are 129 genes annotated, including 84 coding genes, 37 transfer RNA genes (tRNA), and eight ribosomal RNA genes (rRNA).